The Debeli Namet glacier (Durmitor, Montenegro) – from the second half of the 20th century to the present - Djurović, Predrag (Acta geographica Slovenica, 2012)
The Debeli Namet glacier is one of two recent glaciers located in the south western Balkans, located on Durmitor Mountain in the south eastern Dinarides mountain range in Montenegro and is considered to be a small glacier. The size of the glacier from 1954 to 1981 was estimated based on aerial photographs. According to glaciological research, geomorphologic studies of the nearby relief and analyses of climate change (temperature and precipitation) within the last 50 years, new data on the glacier have been obtained. The Debeli Namet glacier is reducing at a rate slower than that of other southern European glaciers. The Debeli Namet glacier did not significantly fluctuate in size (surface and thickness) in response to temperature increases that occurred at the end of the 20 st and at the beginning of the 21st centuries. Here, we present partially revised data accompanied by recent results related to the glacier’s recent behaviour, its surroundings and its associated climate.